Organizational Commitment: Teachers' Perceptions in Turkey - Balyer, Aydin (HACETTEPE UNIV, 2015)
Studies reveal that there is a strong relationship between organizational commitment and staff performance. Organizational commitment is defined as psychological commitment of staff to their organization and addressed as affective, continuance and normative commitment dimensions. This study purposes to discover teachers' perceptions on policies on organizational success, loyalty to the organization, keep working for their organization, organizational values and fate/future of their organizations. This qualitatively study was carried out with 20 teachers from 10 different schools in Istanbul with an interview technique. Results reveal that teachers' perceptions on policies on organizational success, loyalty to the organization, keep working for their organization, organizational values and fate/future of their organizations are low and negative. These results show that there is not healthy organizational culture in the schools of that sample. Therefore, it is recommended that some administrative steps be taken to increase teachers' commitments for achieving success at schools.
Keywords: Organization; organizational commitment; teachers; administrators; CITIZENSHIP BEHAVIOR; JOB-SATISFACTION; TURNOVER; ABSENTEEISM; ANTECEDENTS; SUPPORT; WORKERS; Education & Educational Research